UPAYA GURU DALAM MENANGANI ANAK DISLEKSIA DI SD INTIS SCHOOL YOGYAKARTA - Willa Putri; Muchamad Arif Kurniawan (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2023)
Teachers are not only required to be able to teach in class. However, another important qualification is being able to provide targeted guidance. The lack of teacher knowledge about the difficulties experienced by students is an important thing that must be overcome. One of them is difficulty reading (dyslexia) which is still foreign to teachers in Indonesia. This study aims to determine the efforts of teachers in guiding dyslexic children at SD INTIS School Yogyakarta. This research is a field research based on descriptive qualitative research. Data sources are from the Principal, Teachers in Charge of Inclusion and Classroom Teachers. Data collection techniques through observation and in-depth interviews. The results showed that (1) SD INTIS School Yogyakarta had identified children with dyslexia. With the help of an examination by a psychologist, it can be stated that the child has dyslexia, that is, the child has difficulty in spelling at an age that should be fluent in reading, (2) The efforts made by the teacher to guide dyslexic children are by understanding the child's condition, building the child's self-confidence, and by constantly practicing reading. Even though they haven't used a specific method for dyslexic children, the teacher has used spelling methods and drill methods (practice) which also have an effect on children. In addition, the teacher also takes a personal approach so that children feel they have a place for dyslexic children to tell all of their children's anxieties